PRESENCE OF CATS AS A RISK FACTOR FOR INFECTION WITH TOXOPLASMA GONDII IN DOGS - Morales T., Jackeline (2009)
The objective of the present study was to determine the frequency of the infection with Toxoplasma gondii in two canine populations, those that live together with domestic felines and those which do not; and to determine the risk of infection with T. gondii associated with the presence of domestic felines. A total of 104 samples were evaluated using the Indirect Hemagglutination Test. The results showed that 36.5% (38/104) were positive, while 35% (21/60) and 38.6% (17/44) were dogs that do not live and live with domestic felines respectively and without significant association between the presence of cats and the level of infection. The odds ratio was 1.2 (0.5 – 2.6). There was a significant association of age, breed group, and the freedom of leaving the home with the occurrence of seroreactors to T. gondii. The study showed that the infection in dogs can not be attributed directly to the coexistence with domestic felines and that other ways of spreading the disease must be considered in order to adopt preventive measurements and control of the T. gondii infection.